PENGARUH PEMBELAJARAN TEACHING FACTORY TERHADAP MINAT BERWIRAUSAHA SISWA KELAS XI JURUSAN KULINER SMK NEGERI 3 PEKANBARU - Afridilla, Maharani; Haryana, Gani; Trisnawati, Fenny (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the influence of Teaching factory learning on the entrepreneurial interest of eleventh-grade Culinary Department students at SMK Negeri 3 Pekanbaru. The problem raised in this study is the low entrepreneurial interest among students, which is presumed to be caused by the lack of learning experiences that connect theoretical knowledge with real-world practice. The research method used is a correlational approach quantitative approach with an associative type of study. The population consisted of 104 students, and a sample of 51 students was selected using a proportional random sampling technique. Data were collected through questionnaires to measure entrepreneurial interest and documentation of Teaching factory learning scores. The data were analyzed using simple linear regression to examine the influence of the independent variable on the dependent variable. The results showed that Teaching factory learning had a positive and significant effect on students’ entrepreneurial interest, with a coefficient of determination (R²) of 35,5%. The t-test indicated that Teaching factory learning significantly affected entrepreneurial interest with a significance value of 0.004 < 0.05. These findings emphasize that effective implementation of Teaching factory learning can enhance students’ entrepreneurial interest through contextual learning experiences that foster skills, creativity, and independence.